Football Triple Threat - Jake Maddox (Stone Arch Books, 2023)
Michael has the speed to be a great wide receiver, but he struggles to consistently catch passes. The defensive coach sees potential in Michael's speed and has him try his hand at defensive back. Then the head coach puts Michael on special teams to return kicks. Michael is grateful for all of the opportunities to help his team win, but catching passes continues to trouble him. Can Michael improve his catching and become true triple threat?
Keywords: Sport Stories -- Sport Stories